Dead, mad, or a poet. - Amis, Sara; Saucier, Mark; Pre̜dota, Elinor; Wilson, Catherine M., 1944-; Wendt, Kerry Higgins; Robert, Ben; Hinds, Kathryn, 1962- (Amis, Sara, 2011)
A single issue of this literary journal was published by an Anderson Faery initiate. Originally aimed for being issued at Beltane, the first issue of this biannual would not come to fruition until Lughnasad 2011. This issue featured five poems, a novel excerpt, and an essay and was edited by Sara Amis.
Dead, Mad, or a Poet: A Journal to Faerie
1 electronic document. PDF/A compliant. 776 KB. Includes branding sheet and permission to publish documentation.
Keywords: Essays; Feri (Wiccansect); Marc, Franz, 1880-1916--Poetry; Neopaganism; Periodicals; Persephone (Greek deity)--Poetry; Poetry; Pomegranate--Poetry; Primitivism in literature; Temperance (Tarot)--Poetry; Weather magic--Poetry; Wilson, Catherine M., 1944- When women were warriors; Yeats, W. B. (William Butler), 1865-1939--Criticism and interpretation